Analisis Kalimat Efektif pada Teks Opini dalam Laman “Jawa Pos” Edisi Januari 2025 sebagai Bacaan Edukasi - Alin Nida Millatina; Belia Putri Kunsiyanto; Melly Eka Putpri; Inung Lufiana; Najwa Khalisa Azahra; Asep Purwo Yudi Utomo; Ifutya Warnisa; Desy Rufaidah (BADAN PENERBIT STIEPARI PRESS, 2025)
Education is a process that means a planned effort by someone to influence others, both individuals and groups. Opinion is the response given by someone, which is communication to the communicator who has previously provided a stimulus in the form of a question. Opinion texts contain responses to an event and therefore require supporting arguments and factual sentences that readers can accept; the existence of opinion texts indicates a form of response. The applied solution is to provide knowledge about effective sentences to improve skills in writing opinion texts. Considering its role in effective sentences, research on this is very relevant. Several studies analyze effective sentences. An effective sentence is a sentence that can precisely represent the thoughts or feelings of the speaker or writer and can evoke the same thoughts in the listener or reader as intended by the speaker or writer. The form of the opinion text being analyzed should produce good opinion sentences that adhere to language rules so that the opinion text used for educational media can provide more accurate and easily understood ideas. This research aims to analyze in more depth the effectiveness of using sentences found in opinion texts published on the 'Jawa Pos' website in the January 2025 edition. This analysis will primarily focus on the aspects of structure and word choice (diction) of those sentences. In the Analysis of Effective Sentences in the Opinion Text on the 'Jawa Pos' page for the January 2025 edition as Educational Reading, there is a deep understanding of the syntactic approach encompassing one of the functions, roles, and syntax categories. Using effective sentences in the text can make the text more structured and save words. Syntactic studies that examine the elements present in a sentence have functions, roles, and categories. Generally, each category of words occupies one of its semantic functions and roles.